2012
DOI: 10.1016/j.ultrasmedbio.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Study of Quantitative Ultrasound Parameters in Fatty Rabbit Livers

Abstract: Nonalcoholic fatty liver disease (NAFLD) affects more than 30% of Americans, and with increasing problems of obesity in the United States, NAFLD is poised to become an even more serious medical concern. At present, accurate classification of steatosis (fatty liver) represents a significant challenge. In this study, the use of high-frequency (8 to 25 MHz) quantitative ultrasound (QUS) imaging to quantify fatty liver was explored. QUS is an imaging technique that can be used to quantify properties of tissue givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 56 publications
4
74
0
1
Order By: Relevance
“…20 In that study, a significant and positive correlation was observed between the parameters of the homodyned K-distribution and the FLD stage in rabbits. Another study that used rat models employed Nakagami imaging to examine the relationship between the ultrasound backscattered statistics and the stage of FLD.…”
Section: Research Significancementioning
confidence: 75%
“…20 In that study, a significant and positive correlation was observed between the parameters of the homodyned K-distribution and the FLD stage in rabbits. Another study that used rat models employed Nakagami imaging to examine the relationship between the ultrasound backscattered statistics and the stage of FLD.…”
Section: Research Significancementioning
confidence: 75%
“…The second method uses statistical distributions to model the echo amplitude distribution for a more accurate statistical analysis. This concept has been realized using statistical models, such as K [26] and Nakagami distributions [27,28], indicating that the echo amplitude distribution varies from pre-Rayleigh to Rayleigh with the formation of fatty liver.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these techniques use models of scattering for characterization of tissue disease or response to therapy. [3][4][5][6][7][8][9][10][11] The choice of scattering models is influenced by certain a priori assumptions about the sources of scattering in tissues, such as the assumptions of weak scattering and scattering sites that are physically small compared to a wavelength and, consequently, small compared to the transducer beam width for a weakly focused transducer. This later assumption allows the spatial autocorrelation function of a random medium to be decoupled from the transducer beam.…”
Section: Introductionmentioning
confidence: 99%